KONSTRUKSI MODEL MINAT BERKUNJUNG WISATAWAN MELALUI BRANDING DAN KEPUASAN: STUDI EMPIRIS PADA WISATA BATU BELIMBING KOTA SINGKAWANG - Blikololong, Yohanes Gala Araftake; Sutarto, Sutarto; Saputra, Kasnur; Gloria, Syska (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of brand image and brand awareness on tourists’ intention to visit Batu Belimbing in Singkawang City, with visitor satisfaction as a mediating variable. The background of this research is the increasing competition among coastal tourism destinations, which requires branding-based marketing strategies to attract tourist interest. A quantitative approach was applied through a survey method, with primary data collected from 100 respondents using a structured questionnaire. The data were analyzed using path analysis with the assistance of SPSS software. The findings reveal that brand image and brand awareness have a significant direct influence on visitor satisfaction and visit intention. Moreover, visitor satisfaction is proven to significantly mediate the relationship between brand image and brand awareness on tourists’ visit intention. These results highlight the crucial role of branding efforts and satisfying visitor experiences in shaping tourist decision-making. Practically, this study provides insights for destination managers to enhance competitiveness and increase tourist visits through stronger branding strategies and improved service quality.